Zebrafish models for dyskeratosis congenita reveal critical roles of p53 activation contributing to hematopoietic defects through RNA processing. - Ying Zhang (Public Library of Science (PLoS), 2012)
Dyskeratosis congenita (DC) is a rare bone marrow failure syndrome in which hematopoietic defects are the main cause of mortality. The most studied gene responsible for DC pathogenesis is DKC1 while mutations in several other genes encoding components of the H/ACA RNP telomerase complex, which is involved in ribosomal RNA(rRNA) processing and telomere maintenance, have also been implicated. GAR1/nola1 is one of the four core proteins of the H/ACA RNP complex. Through comparative analysis of morpholino oligonucleotide induced knockdown of dkc1 and a retrovirus insertion induced mutation of GAR1/nola1 in zebrafish, we demonstrate that hematopoietic defects are specifically recapitulated in these models and that these defects are significantly reduced in a p53 null mutant background. We further show that changes in telomerase activity are undetectable at the early stages of DC pathogenesis but rRNA processing is clearly defective. Our data therefore support a model that deficiency in dkc1 and nola1 in the H/ACA RNP complex likely contributes to the hematopoietic phenotype through p53 activation associated with rRNA processing defects rather than telomerase deficiency during the initial stage of DC pathogenesis.